Thiamethoxam Resistance in Aphis gossypii Glover Relies on Multiple UDP-Glucuronosyltransferases - Pan, Yiou; Tian, Fayi; Wei, Xiang; Wu, Yongqiang; Gao, Xiwu; Xi, Jinghui; Shang, Qingli (Frontiers in Physiology, 2018)
Uridine diphosphate (UDP)-glycosyltransferases (UGTs) are major phase II enzymes that conjugate a variety of small lipophilic molecules with UDP sugars and altering them into more water-soluble metabolites. Therefore, glucosidation plays a major role in the inactivation and excretion of a great variety of both endogenous and exogenous compounds. In this study, two inhibitors of UGT enzymes, sulfinpyrazone and 5-nitrouracil, significantly increased the toxicity of thiamethoxam against the resistant strain of Aphis gossypii, which indicates that UGTs are involved in thiamethoxam resistance in the cotton aphid. Based on transcriptome data, thirty-one A. gossypii UGTs that belong to 11 families (UGT329, UGT330, UGT341, UGT342, UGT343, UGT344, UGT345, UGT348, UGT349, UGT350 and UGT351) were identified. Compared with the thiamethoxam-susceptible strain, the transcripts of 23 UGT genes were elevated, with the transcripts of 13 UGT genes (UGT344J2, UGT348A2, UGT344D4, UGT341A4, UGT343B2, UGT342B2, UGT350C3, UGT344N2, UGT344A14, UGT344B4, UGT351A4, UGT344A11 and UGT349A2) increasing by approximately 2.0-fold higher in the resistant cotton aphid. The suppression of selected UGTs significantly increased the insensitivity of resistant aphids to thiamethoxam, suggesting that the up-regulated UGTs may be associated with thiamethoxam tolerance. This study provides an overall view of the possible metabolic-factors UGTs relevant to the development of insecticide resistance. The results may facilitate further work to validate the roles of these UGTs in thiamethoxam resistance.